2016
DOI: 10.4103/0975-962x.184649
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nickel release from various dental appliances used routinely in pediatric dentistry

Abstract: Context:The use of nickel-containing alloys in dentistry has been questioned because of the biological liabilities of nickel and the release of nickel ions from dental appliances into the oral cavity. The potential health hazards of nickel and chromium and their compounds have been the focus of attention for more than 100 years. It has established that these metals could cause hypersensitivity.Aims:To assess the nickel release from various dental appliances used in pediatric dentistry.Settings and Design:It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…66,No. 1 This is in accordance with the studies of Kulkarni et al (33) who assessed the Ni release over 4 weeks and asserted that the peaks around the 1day that decrease gradually afterwards, and Ramazani et al (52) who studied the Ni release over a month and asserted that the peak of ion level is on the 1day which declined to less than the half in the 7 day, and then reached zero in further intervals.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…66,No. 1 This is in accordance with the studies of Kulkarni et al (33) who assessed the Ni release over 4 weeks and asserted that the peaks around the 1day that decrease gradually afterwards, and Ramazani et al (52) who studied the Ni release over a month and asserted that the peak of ion level is on the 1day which declined to less than the half in the 7 day, and then reached zero in further intervals.…”
Section: Discussionsupporting
confidence: 83%
“…Fig 1A. Each group was placed in a numbered sterilized closed glass container containing 50 ml of artificial saliva with a pH of 6.43 ± 0.26 ( fig 1B). The formula of artificial saliva was 0.8 g NaCl, 2.4 g KCl, 1.5 g NaH2PO4, 0.1 g Na2S, and 2 g CO[NH2]2), that stored in an incubator at 37°C for 4 weeks (33) . Any adjustment for the standard pH value is required, an increment of 1N sodium hydroxide or 1 N hydrochloric was added (34) .…”
Section: I-in-vitro Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva is rich in chloride ions, and the presence of sodium chloride may result in pitting/corrosion of stainless-steel surfaces if they are scratched or nicked [44]. Similar results have been released by other researchers [45,46]. Morán-Martínez et al reported that a significant increase in Ni level was observable among urine samples collected over time [47].…”
Section: Discussionsupporting
confidence: 62%
“…The contact surface of metals in this type of corrosion is very important. The weaker metal (anode) is corroded in this process [26].…”
Section: Introductionmentioning
confidence: 99%